The crystal and molecular structures of three copper‐containing complexes and their activities in mimicking galactose oxidase. Issue 5 (10th April 2019) - Dimeska, Roza; Wikaira, Jan; Mockler, Garry M.; Butcher, Ray J.
Abstract : The structures of three copper‐containing complexes are reported and tests for their activity in the oxidation ofd ‐galactose suggest that, unlike the enzyme galactose oxidase, due to the precipitation of Cu2 O, this reaction is not catalytic as would have been expected. Abstract : The structures of three copper‐containing complexes, namely (benzoato‐κ 2 O, O ′)[( E )‐2‐({[2‐(diethylamino)ethyl]imino}methyl)phenolato‐κ 3 N, N ′, O ]copper(II) dihydrate, [Cu(C7 H5 O2 )(C13 H19 N2 O)]·2H2 O, 1, [( E )‐2‐({[2‐(diethylamino)ethyl]imino}methyl)phenolato‐κ 3 N, N ′, O ](2‐phenylacetato‐κ 2 O, O ′)copper(II), [Cu(C8 H7 O2 )(C13 H19 N2 O)], 2, and bis[μ‐( E )‐2‐({[3‐(diethylamino)propyl]imino}methyl)phenolato]‐κ 4 N, N ′, O : O ;κ 4 O : N, N ′, O ‐(μ‐2‐methylbenzoato‐κ 2 O : O ′)copper(II) perchlorate, [Cu2 (C8 H7 O2 )(C12 H17 N2 O)2 ]ClO4, 3, have been reported and all have been tested for their activity in the oxidation ofd ‐galactose. The results suggest that, unlike the enzyme galactose oxidase, due to the precipitation of Cu2 O, this reaction is not catalytic as would have been expected. The structures of1 and2 are monomeric, while3 consists of a dimeric cation and a perchlorate anion [which is disordered over two orientations, with occupancies of 0.64 (4) and 0.36 (4)]. In all three structures, the central Cu atom is five‐coordinated in a distorted square‐pyramidal arrangment (τ parameter of 0.0932 for1, 0.0888 for2, and 0.142 and 0.248 for the two Cu centers in3 ). In each species, the environment about the Cu atom is such that the vacant sixth position is open, with very little steric crowding.